Developing social strategies to overcome peer rejection of children with Attention Deficit Hyperactivity Disorder - Jenkins, Heather; Batgidou, Ekaterina (Learning Difficulties Australia, 2003)
Investigation of 265 children's attitudes towards vignettes of Year 5 peers with Attention Deficit Hyperactivity Disorder (ADHD) revealed strong rejection of Hyperactive and Combined subtypes, relative to Inattentive subtypes and non-ADHD controls. The social difficulties of children with ADHD may be understood within Barkley's theoretical model of ADHD (Barkley, 1997) that links deficits in response inhibition with four executive neuropsychological functions contributing to social cognition. The theory is also helpful in predicting strategies that may be facilitated by teacher intervention to construct improved social relationships among children with and without ADHD.